Environmentally friendly equilibrium strategy for coal distribution center site selection. (10th February 2020) - Dai, Jingqi; Xie, Yachen; Xu, Jiuping; Lv, Chengwei
Abstract: Coal distribution centers play an important role in the coal supply chain by linking up coal producers with its users. However, with increasing attention on environmental protection issues, coal distribution centers need to focus on their environmental impacts during the construction and operation process. This paper develops an integrated approach to achieve the environmentally-friendly coal distribution sites selection process. In this study, suitable candidate sites were first selected by employing big data tools and Geographical Information Systems (GIS) technology, then an equilibrium strategy based multi-objective bi-level model was proposed to resolve the potential conflicts of interest between authority and the collieries. This model pursued maximum revenue and minimum coal dust emissions in order to achieve harmonious development of both the economy and the environment, and it was simplified into an easier calculation form with interactive solutions. The proposed method was then proven to be applicable by providing practical application from China and analyzing the computational results under different scenarios. Recommendations at the managerial level based on this methodology could assist administrators in different regions to make informed decisions and develop reasonable policies. Highlights: An equilibrium strategy is proposed to solve coal distribution center site selection. A bi-level multi-objective model is built to solve economy and ecology conflict. The uncertainty is considered and the trapezoidal fuzzy number is used. The proposed method is proved applicable and effective with real case. Some management suggestions are given to help managers make appropriate policies.